Analisis faktor yang memengaruhi kesiapan menikah wanita dewasa awal yang mengalami trust issues dalam hubungan romansa - Putra, Ade Herdian; Ardi, Zadrian; Mudjiran, Mudjiran; Rahmaini, Indah Sari (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2024)
Ideally, in the early adult development stage, women are able to find a partner and build a family life. However, this can be hampered when early adult women experience trust issues in romantic relationships. Trust issues in romantic relationships can reduce the level of readiness for marriage in early adult women. This study aims to examine the correlation of several factors that are predicted to have a correlation with the readiness to marry early adult women who experience trust issues in romantic relationships. This study uses a quantitative approach with correlational methods. This study involved 152 young adult women who were categorized as experiencing trust issues in romantic relationships. Data analysis used structural equation model-partial least square analysis. Based on research data analysis, readiness to have sexual relations and intimate communication skills are positively and significantly correlated with readiness to marry early adult women who experience trust issues in romantic relationships. However, this study also found that social environment support and family support did not significantly correlate with readiness for marriage in early adult women who experienced trust issues in romantic relationships. These findings can be a reference for further research with the same theme and references in psychological services with related clients.